Acute pancreatitis: pancreas divisum with ventral duct intraductal papillary mucinous neoplasms. (7th October 2014) - Gurram, Krishna C; Czapla, Agata; Thakkar, Shyam
Abstract : Acute recurrent pancreatitis occurs rarely in individuals with pancreas divisum. A 39-year-old woman with no significant history presented with pancreatitis. CT scan and MRI suggested acute on chronic pancreatitis with calcifications and pancreatic divisum. An endoscopic ultrasound demonstrated complete pancreas divisum. A large calcification measuring 12 mm × 6 mm was seen in the head of the pancreas with associated dilation of the ventral pancreatic duct. Fine-needle aspiration of the dilated ventral pancreatic duct showed an amylase level of 36 923 U/L and a carcinoembryonic antigen of 194. A ventral duct intraductal papillary mucinous neoplasm was suspected and a pancreaticoduodenectomy procedure was recommended. After the procedure, pathology demonstrated an intraductal papillary lesion in the main duct with moderate dysplasia. A pancreatic intraepithelial neoplasia, grade 2 was also present. Margins of resection were clear. This case represents the importance of assessing for secondary causes of pancreatitis in pancreas divisum.